Visions of Childhood, Notions of Rurality, and Anti-bias Education: Emerging Educators Strive for Praxis - Emily A. Nemeth; Heather Hill (The University of Alabama, 2022)
The work of anti-bias educators is becoming increasingly important across educational landscapes in the United States. While this work is well-documented within K-12 schools, less known are the efforts of educators working on the front lines of the anti-bias educational agenda within out-of-school time (OST) programs. In an effort to explore how this work happens in OST programs, we partnered with Read, a summer literacy program serving children in grades K-8. Through an engaged research framework, we asked what factors mediated their delivery of an anti-bias education in the Read program. Two significant findings emerged. First, White parents and caregivers in rural settings were a significant force shaping curricular decisions. Second, conceptualizations of childhood influenced teaching and learning. We offer implications for practice and research and conclude by discussing future directions of anti-bias education in these sites of teaching and learning.